Dual pathways to prospective remembering - McDaniel, Mark A.; Umanath, Sharda; Einstein, Gilles O.; Waldum, Emily R. (Frontiers in Human Neuroscience, 2015)
According to the multiprocess framework (McDaniel & Einstein, 2000), the cognitive system can support prospective memory (PM) retrieval through two general pathways. One pathway depends on top-down attentional control processes that maintain activation of the intention and/or monitor the environment for the triggering or target cues that indicate that the intention should be executed. A second pathway depends on (bottom-up) spontaneous retrieval processes, processes that are often triggered by a PM target cue; critically spontaneous retrieval is assumed to not require monitoring or active maintenance of the intention. Given demand characteristics associated with experimental settings, however, participants are often inclined to monitor, thereby potentially masking discovery of bottom-up spontaneous retrieval processes. In this article, we discuss parameters of laboratory PM paradigms to discourage monitoring and review recent behavioral evidence from such paradigms that implicate spontaneous retrieval in PM. We then re-examine the neuro-imaging evidence from the lens of the multiprocess framework and suggest some critical modifications to existing neuro-cognitive interpretations of the neuro-imaging results. These modifications illuminate possible directions and refinements for further neuro-imaging investigations of PM.